THE EFFECTIVENESS OF SCHOOL PRINCIPAL LEADERSHIP IN ENHANCING TEACHER PROFESSIONAL COMPETENCE AT SMK MIFTAHUL ULUM TUMPENG WONOSARI, BONDOWOSO - Sitti Nuraini (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2024)
Effective leadership of school principals is considered a crucial factor in creating a supportive learning environment. This study aims to investigate the effectiveness of the principal's leadership in enhancing teachers' professional skills at SMK Miftahul Ulum Tumpeng Wonosari, Bondowoso. The method used is a qualitative descriptive approach, utilizing data collection techniques through observation, interviews, and documentation. The researcher observed the effectiveness of the principal's leadership by taking notes and recordings. Additionally, the researcher conducted interviews with the principal, teachers, and administrative staff at SMK Miftahul Ulum. Once the data was collected, the researcher performed data reduction, classification, validation, and coding based on the data types, followed by interpretation. The results showed that there were three aspects observed in the principal's leadership at SMK Miftahul Ulum, namely strategies to improve teachers' professional competence, challenges faced in this process, and the impact of the principal's leadership on enhancing teachers' professional competence. The strategies to enhance teachers' competence include training programs, workshops, performance assessments, and evaluations. Meanwhile, the challenges faced include global competition and changes in the educational curriculum. The positive impact of the principal's leadership is evident in the improvement of teachers' teaching quality, the creation of a conducive work environment, and the enhancement of students' academic achievements. Thus, this study concludes that the principal's leadership at SMK Miftahul Ulum Tumpeng has proven effective in improving teachers' professional competence. These findings provide practical implications for other educational institutions in efforts to improve education quality by focusing on teacher competence development. The suggested recommendations include increasing policy support, allocating adequate resources, and enhancing the frequency and quality of professional development programs.